History of the manhattan water-works - Adams, Samuel John (My University, 1898)
Introduction: In studying the history of the Manhattan water-works it is interesting to notice the arguments that were used to induce the people to vote bonds for the works. So far as I have been able to find the first article on the subject of city waterworks which appeared in the principle paper of the city, was in the issue of December 31, 1886. This article was under the headlines, “Lets Have a Boom,” and reads as follows:
Citation: Adams, Samuel John. History of the manhattan water-works. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Manhattan; History; Water-works; Theses; Manuscripts (documents)